CGIAR Initiative on Agroecology: Technical report on the types, availability, quantities and spatial distribution of organic resources in Kiambu and Makueni Counties - Kuria, Anne; Wamaitha, Mercy; Mwangi, Victor; Onyango, Kevin; Bolo, Peter; Wanyama, Rosina; Adoyo, Beatrice; Fuchs, Lisa Elena; Korir, Hezekiah; Lelei, David; Awiti, Alex (2024)
Organic resources are a critical entry point for fostering agroecological transitions. They contribute to soil health, nutrient cycling, and biodiversity conservation, enhancing agricultural sustainability and resilience. Three primary sources are animal manure, crop residues, and purpose-produced organic resources from agroforestry. A systematic mapping initiative focused on these sources holds immense potential to facilitate informed decision-making, optimize resource utilization, and promote adopting agroecological practices across Kenya ALLs. We propose a systematic mapping of organic resources within agricultural landscapes, emphasizing animal manure, crop residues, and purpose-produced organic resources from agroforestry. This technical report presents results from a survey that was undertaken to identify and quantify the spatial distribution of organic resources that exist within the entire Kiambu and Makueni counties. Specific objectives: 1. To characterize the socio-economic profiles of communities in Kiambu and Makueni Counties. 2. To analyze the types and composition of organic resources, including their volumes, frequency of production, availability, uses, benefits, reasons for use, potential substitutes, outsourcing and purchasing costs, as well as sales and income generation. 3. To identify the challenges, opportunities, and solutions related to organic resource utilization, including implemented and unimplemented solutions and the barriers to their implementation. 4. To assess the existing skills of the Kiambu and Makueni county populations related to organic resource management, identify skill gaps, and determine training needs.